Knowledge and Willingness to Practice Chairside Buffering of Local Anaesthesia among Nigerian Dental Practitioners: A Cross-Sectional Study (Nigerian Dental Journal, 2026)
Background: Local anesthetic (LA) chairside buffering has been documented to reduce injection pain, shorten onset time, and improve patient comfort during dental procedures. Consequently, dental practitioners' knowledge and practice of LA buffering could significantly improve dental practice and enhance patients' attendance at dental clinics. This study assesses the knowledge and willingness among dental practitioners in Nigeria to practice chairside LA buffering.Methods: This cross-sectional study was conducted over 6 months (November 2024 to April 2025). Participants were recruited after obtaining consent and completing a self-administered questionnaire consisting of two domains: knowledge and willingness to practice. The knowledge domain consisted of 10 questions asking participants to select "Yes," "No," or "I do not know" for each question, and each correct response was scored 1 mark, while a wrong or "I do not know" answer scored 0 mark. Total knowledge scores were categorized as low (≤50%), fair (51–69%), or good (≥70%). Five questions were asked in the willingness to practice domain, and responses were analyzed in the order they were asked. Data were analyzed using IBM SPSS software version 25.Results: A total of 158 respondents completed the questionnaire, giving a response rate of 98.1%. The sample comprised 106 (67.1%) males and 52 (32.9%) females. Most respondents, 96 (60.8%), were in the age range of 31–40 years, and 155 (98.1%) had been practicing for more than 2 years. Resident doctors constituted the highest respondents (80, 50.6%), and the majority (125, 79.1%; 95% CI: 72.0–85.1%) were aware of LA chairside buffering. The overall mean knowledge score was 38.4%, and the majority of respondents (153, 96.8%; 95% CI: 92.9–98.8%) had never practiced chairside buffering of LA, with only 54 (34.2%; 95% CI: 26.9–42.1%) willing to practice it. No statistically significant difference was found between gender and willingness to practice chairside LA buffering (χ² = 0.632, df = 1, p = 0.426). The main reason for not willing to practice buffering of LA was extra cost of treatment (45, 43.3%).Conclusion: While the benefit of chairside LA buffering in providing less painful, more reliable, and comfortable anesthesia has been established, knowledge, practice, and willingness to practice this technique among dentists were found to be low.Keywords: Local anesthetic buffering, Chairside, Knowledge, Dental practitioners